2017
DOI: 10.5194/aab-60-71-2017
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional quality of kermes oak (<i>Quercus coccifera</i> L.) acorns as affected by altitude in a typical Mediterranean area

Abstract: Abstract. The impact of altitudinal zone on the nutritional quality of kermes oak (Quercus coccifera L.) acorns was assessed in Xirovouni Mountain shrublands in northwestern Greece. Whole acorns were collected during autumn 2011 from 15 sites located at three altitudinal zones (i.e. lower, middle, upper). Kermes oak acorn samples were manually separated into kernel and hull and analysed for chemical composition (crude protein, CP; neutral detergent fibre, NDF; acid detergent fibre, ADF; lignin), in vitro dry m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…The comparison between the kermes oak and mock privet in terms of Zn content revealed that the mock privet had a higher Zn content than the kermes oak, and the Zn contents were within the range of 17.07-37.83 mg/kg. In a study, it was reported that the Zn content in the trunk of kermes oak varied within the range of 3.00-5.90 mg/kg depending on the altitude (Roukos et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The comparison between the kermes oak and mock privet in terms of Zn content revealed that the mock privet had a higher Zn content than the kermes oak, and the Zn contents were within the range of 17.07-37.83 mg/kg. In a study, it was reported that the Zn content in the trunk of kermes oak varied within the range of 3.00-5.90 mg/kg depending on the altitude (Roukos et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The Cu content in shrubs varies depending on the plant species, maturity period, season, and soil characteristics (Gökkuş et al, 2013). In a study, it was reported that the Cu content in the kermes oak differed depending on the altitude and was different in the trunk and acorn, and the Cu content in the kermes oak acorn varied within the range of 1.60-2.80 mg/kg depending on the altitude (Roukos et al, 2017). The iron (Fe) content was found to be 161.30 mg/kg in kermes oak and 133.4 mg/kg in mock privet (p<0.01).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the studies worked on different oak species on dry matter digestibility without concerning seasonal variation (13,27) and on the nutritive value with ADF and NDF (13,24). Besides, there are several studies that focused on the nutrient content (10,13,15,26), fatty acid profile (6,11,20,23,29) and in vitro digestibility (10,(25)(26)(27)34) of different species and parts of oak. A study (22) that was encountered in the relevant literature sampled on the main and lateral branch and fresh twigs with leaves of kermes.…”
Section: Introductionmentioning
confidence: 99%
“…Despite its low commercial value with regard to wood production, it plays a significant role in preventing soil erosion [21], and it is used for fodder production for domestic and wild animals [22]. Kermes oak acorns seem to be a highly energetic resource for small ruminants such as goats and lambs and are often compared to barley [23,24].…”
Section: Introductionmentioning
confidence: 99%